Gazing at r-star: A hysteresis perspective - Paul Beaudry; Katya Kartashova; Césaire Assah Meh (Bank of Canada, 2023)
Many explanations for the decline in real interest rates over the last 30 years point to the role that population aging or rising income inequality plays in increasing the long-run aggregate demand for assets. Notwithstanding the importance of such factors, the starting point of this paper is to show that the major change driving household asset demand over this period is instead an increased desire-for a given age and income level-to hold assets. We begin by presenting a simple explanation for this pattern that relies on integrating retirement and intertemporal substitution motives in saving decisions. We then show how the interaction of these two saving motives can have profound implications in terms of the shape of asset demands, the possibility of multiple steady state real interest rates, and a potential role for monetary policy to influence the long-run evolution of real rates. The framework highlights how an inflationary episode followed by a strong monetary response, as we are currently witnessing, can have long-term implications for real interest rates.
Keywords: E21; E52; E31; E43; E58; E62; G51; H6; 330; Monetary policy; Interest rates; Inflation targets; Monetary policy framework; Inflation andprices; Fiscal policy; Economic models